(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2011)
The efficiency of applying magnetic survey in chromite fields is substantiated. It was pointed, that in Shorja ore field local anomalies of negative and relative minimums of magnetic field are caused by spatial distribution of chromite ore bodies.